NEW TREND IN EDUCATION: BITE-SIZED LEARNING - Singh, Neetu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Learning is a relatively lasting change in behavior that is the result of experience. It is the acquisition of information, knowledge, and skills. Traditional learning methods often overwhelm learners with large volumes of information, leading to cognitive overload and reduced retention. It typically takes place in a classroom setting, where a teacher delivers information to students over an extended period of time. The traditional classroom setting, once the cornerstone of education, is being challenged by more modern approaches like Bite-sized learning. Bite-sized learning combats this by focusing on one concept at a time, ensuring that learners can fully grasp and remember the material. Bite-Sized Learning is a shift from traditional learning and is getting popularized in recent years. There are many benefits of Bite-sized learning which have been discussed in this paper.